Matter scattering in quadratic gravity and unitarity. (16th March 2018) - Abe, Yugo; Inami, Takeo; Izumi, Keisuke; Kitamura, Tomotaka
Abstract: We investigate the ultraviolet (UV) behavior of two-scalar elastic scattering with graviton exchanges in higher-curvature gravity theory. In Einstein gravity, matter scattering is shown not to satisfy the unitarity bound at tree level at high energy. Among some of the possible directions for the UV completion of Einstein gravity, such as string theory, modified gravity, and inclusion of high-mass/high-spin states, we take R_μν^2 gravity coupled to matter. We show that matter scattering with graviton interactions satisfies the unitarity bound at high energy, even with negative norm states due to the higher-order derivatives of metric components. The difference in the unitarity property of these two gravity theories is probably connected to that in another UV property, namely, the renormalizability property of the two.